Dual-fuel diesel engines - Karim, G. A. (CRC Press, 2015)
This book offers an integrated and balanced discussion of the different types of gaseous fuels that can be used within dual fuel diesel engines. It presents a comprehensive and well-integrated review of the relevant fundamentals and practices of the operation of gas-fueled diesel engines of the dual fuel type in their variety of sizes and fields of application. The book highlights both positive features and potential challenges, providing an outline of measures for optimizing performance and overcoming issues.